Intelligent metadata web search engines: A brief review of literature on intelligent metadata based search engines - Mahdi M.N.; Ahmad A.R.; Ismail R. (Institute of Electrical and Electronics Engineers Inc., 2023)
Information retrieval; Intelligent agents; Internet; Metadata; Social networking (online); Websites; World Wide Web; Amount of information; Data; Digital world; Internet users; Meta search engines; Search engines